Comparative Evaluation of Vitek 2 and Etest versus Broth Microdilution for Ceftazidime/Avibactam and Ceftolozane/Tazobactam Susceptibility Testing of Enterobacterales and Pseudomonas aeruginosa - Arhodoula Papadomanolaki; Maria Siopi; Polyxeni Karakosta; Sophia Vourli; Spyros Pournaras (MDPI AG, 2022)
Ceftazidime/avibactam (CZA) and ceftolozane/tazobactam (C/T) are novel antibiotics with activity against multidrug-resistant Gram-negative pathogens. Nevertheless, resistance to both agents has been reported emphasizing the need for accurate and widely accessible susceptibility testing. In the present study, Vitek 2 and Etest CAZ and C/T MIC results for 100 non-repetitive clinical isolates (83 Enterobacterales and 17 P. aeruginosa, whereof 69 challenge isolates) were compared to the standard broth microdilution (BMD) method. EUCAST breakpoints were used for assessing the categorical (CA) and essential (EA) agreement between the methods along with the corresponding error rates. The Vitek 2 performance was comparable to that of BMD for testing both antimicrobial agents exceeding the ISO requirements (CA 98-99%, EA 96-100%, major errors (MEs) 0-1%, very major error (VMEs) 1%). Likewise, the Etest provided accurate results for CZA and C/T testing against Enterobacterales and P. aeruginosa, respectively (CA 100%, EA 97-100%, MEs 0%, VMEs 0%). On the contrary, EA of 85% and 6% VME rate were found for CZA Etest and P. aeruginosa. Overall, Vitek 2 measurements of CZA and C/T susceptibility correlated closely with the reference BMD, indicating that it can represent a suitable alternative to BMD for susceptibility testing of Enterobacterales and P. aeruginosa. The Etest did not fulfill the ISO performance criteria of EA and VME for CZA and P. aeruginosa. Further studies are needed to assess whether the Etest allows a reliable assessment of CZA and C/T EUCAST MICs.